KHULU' DAN TALAK, SAMAKAH? Kajian Filosofis-Komparatif Hak Cerai Perempuan dalam Fiqh dan Hukum Positif - Fathonah K. Daud (Al Hakam : The Indonesian Journal of Islamic Family Law and Gender Issues, 2021)
This paper is a philosophical-comparative study of Islamic law in Islam and in the provisions of Positive Law. Are the discussions and provisions the same between khuluc and talak in fiqh and positive law? This research is a descriptive-qualitative research, using a literature review approach and analyzing it with the deduction method. The findings of this study indicate that khuluc in Indonesian law is called a divorce suit with different procedures. Both fiqh and positive law do not give the same meaning between khuluc (here called fasakh) and talak, this is the opinion of the Syafi'i school, except in Imam Malik's view that khuluc is talak bain. Therefore, the two have different legal provisions after the divorce. For example, for groups that distinguish the two, after the khulu’ occurs, they may be reconciled again. Meanwhile, those who equate khulu’ with talak bain, after khulu 'are prohibited from making reconciliation for ex-husbands and wives. However, between khulu 'and talak are different. Khulu’ occurs there must be 'iwad, while divorce there is no' iwad.